2017
DOI: 10.1038/s41559-017-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic genome evolution in a recent and rapid avian radiation

Abstract: Recent genomic analyses of evolutionary radiations suggest that ancestral or standing genetic variation may facilitate rapid diversification, particularly in cases involving convergence in ecological traits. Likewise, lateral transfer of alleles via hybridization may also facilitate adaptive convergence, but little is known about the role of ancestral variation in examples of explosive diversification that primarily involve the evolution of species recognition traits. Here, we show that genomic regions disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 100 publications
6
113
1
Order By: Relevance
“…Divergence between the species was widely distributed across the genome based on the distribution of fixed SNPs and d XY and F ST values. This contrasts with many recent studies in birds that have found isolated regions of elevated divergence, and often support for the importance of those regions in reproductive isolation (e.g., Poelstra et al, 2014;Küpper et al, 2016;Tuttle et al, 2016;Campagna, Gronau, Silveira, Siepel, & Lovette, 2015;Toews et al, 2016;Oswald et al, 2016;Stryjewski & Sorenson, 2017). Many of those studies, however, involved taxa that likely experienced episodes of contact and introgression during the history of species formation.…”
Section: Divergence Among Species and Across The Genomementioning
confidence: 63%
“…Divergence between the species was widely distributed across the genome based on the distribution of fixed SNPs and d XY and F ST values. This contrasts with many recent studies in birds that have found isolated regions of elevated divergence, and often support for the importance of those regions in reproductive isolation (e.g., Poelstra et al, 2014;Küpper et al, 2016;Tuttle et al, 2016;Campagna, Gronau, Silveira, Siepel, & Lovette, 2015;Toews et al, 2016;Oswald et al, 2016;Stryjewski & Sorenson, 2017). Many of those studies, however, involved taxa that likely experienced episodes of contact and introgression during the history of species formation.…”
Section: Divergence Among Species and Across The Genomementioning
confidence: 63%
“…Loci with <20% missing genotypes were retained for downstream analyses, and final output files (e.g., fasta, NEXUS, ADMIXTURE) were generated with custom python scripts (Lavretsky et al, ). Input files for fineRADstructure analyses were created using a custom python script from Stryjewski and Sorenson ().…”
Section: Methodsmentioning
confidence: 99%
“…Arrows highlight two samples consistently identified as admixed across PCA, admixture, and fineRADstructure (see Figure 3) analyses python scripts . Input files for fineRADstructure analyses were created using a custom python script from Stryjewski and Sorenson (2017).…”
Section: Sampling Dna Extraction Library Preparation and Data Prmentioning
confidence: 99%
“…Increasing evidence from genomewide studies suggests that ancestral and heterospecific genetic variation plays an important role in the evolution of phenotypic diversity (Abbott et al., ; Cui et al., ; Racimo, Sankararaman, Nielsen, & Huerta‐Sánchez, ; Stryjewski & Sorenson, ; The Heliconius Genome Consortium, ). Different phenotypes and different regions within the same genome often show discordant patterns of divergence, suggesting that they followed different evolutionary trajectories, most of which do not follow the species tree.…”
Section: Introductionmentioning
confidence: 99%
“…Such adaptive introgression may be restricted to single genome regions and single components of phenotypes. However, plumage phenotypes in Munia finches and wing‐colour patterns in Heliconius butterflies, for instance, suggest that repeated, multidirectional introgression of entire toolkits of genomic regions may constitute an important pathway towards the rapid evolution of mosaic phenotypes (Stryjewski & Sorenson, ; Van Belleghem et al., ). Regardless of the proportion of the genome involved, introgression upon hybridization is increasingly proving to be an important contributor to evolutionary novelty (Abbott et al., ; Rheindt & Edwards, ) and may fuel entire adaptive radiations, such as the one of east African cichlid fish (Meier et al., ).…”
Section: Introductionmentioning
confidence: 99%